2019
DOI: 10.1007/s10681-019-2505-3
|View full text |Cite|
|
Sign up to set email alerts
|

Factor analysis to investigate genotype and genotype × environment interaction effects on pro-vitamin A content and yield in maize synthetics

Abstract: Vitamin A Deficiency (VAD) is a major public health problem in Sub-Saharan Africa affecting 33 million preschool-age children. Enrichment of maize varieties with provitamin A could provide sustainable and affordable solution to VAD. This study was conducted to understand the extent of GEI effects on both grain yield and provitamin A content in 21 maize synthetics and identify synthetics combining stable performance with high level provitamin A content across diverse environments in West Africa. Combined analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…In these cases, the SH × environment interaction component was greater than the genetic variance component in most of the crop seasons. This is very frequent in most of the situations in which various hybrids are evaluated in the same crop season (Tonk et al, 2011;Nzuve et al, 2013;Ndhlela et al, 2014;Mengesha et al, 2019). In the conditions evaluated, the significant effect of the interaction is expected due to the expressive environmental variation of numerous factors, such as climate, soil fertility, and management practices that occurs in the different locations in which maize experiments are conducted (Noia Junior et al, 2019;Embrapa, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the SH × environment interaction component was greater than the genetic variance component in most of the crop seasons. This is very frequent in most of the situations in which various hybrids are evaluated in the same crop season (Tonk et al, 2011;Nzuve et al, 2013;Ndhlela et al, 2014;Mengesha et al, 2019). In the conditions evaluated, the significant effect of the interaction is expected due to the expressive environmental variation of numerous factors, such as climate, soil fertility, and management practices that occurs in the different locations in which maize experiments are conducted (Noia Junior et al, 2019;Embrapa, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Dawson et al (2013) made genomic predictions within groups of environments clustered using several methods, and of those reported, the FA model had superior accuracy across environments with differing levels of genetic correlation. Mengesha et al (2019) used the FA model to identify stability and adaptability of maize varieties as it related to both grain yield and provitamin A content. This study showed that the FA model can be applied to FN, a wheat end-use quality trait.…”
Section: Discussionmentioning
confidence: 99%
“…Mengesha et al. (2019) used the FA model to identify stability and adaptability of maize varieties as it related to both grain yield and provitamin A content. This study showed that the FA model can be applied to FN, a wheat end‐use quality trait.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biosynthesis and accumulation of carotenoids in crops are modulated both by the crop genotype and environmental factors [ 27 , 28 ]. Studies have demonstrated that many factors, including soil type, temperature, moisture, light intensity, occurrence of biotic and abiotic stresses, altitude, maturity cycle, and cropping practices significantly affect the synthesis and accumulation of individual carotenoids in maize and other crops [ 23 , 27 , 29 , 30 , 31 , 32 , 33 ]. Consequently, evaluating provitamin A biofortified maize hybrids involving diverse parents with medium to high provitamin A content, across variable climatic and other field growing conditions, is critical to elucidate the nature of the relationship between provitamin A accumulation and agronomic performance.…”
Section: Introductionmentioning
confidence: 99%